تأثير العوامل المتعلِّقة بالعميل على قرار منح الائتمان الصَّغير دراسة ميدانيَّة على المؤسَّسات الماليَّة العاملة في السَّاحل السُّوري - حسون, عتاب (Latakia University Journal - Economic and Legal Sciences Series, 2018)
جاء هذا البحث للوقوف على مدى تأثير العوامل المتعلِّقة بالعميل (شخصيَّة العميل وسمعته، قدرة العميل وخبرته العمليَّة، المركز المالي للعميل، الضَّمانات المقدَّمة من قبل العميل والعوامل الاقتصاديَّة والسِّياسيَّة المحيطة بالعميل) على قرار منح الائتمان المصرفي الصَّغير للأفراد والمشروعات الصَّغيرة، وذلك في عيِّنة من المؤسَّسات الماليَّة العاملة في السَّاحل السوري. قامت الباحثة بتوزيع (135) استبياناً على عيِّنة من العاملين في قسم الائتمان في المؤسَّسات الماليَّة محل الدراسة، وقد بلغ عدد الاستبانات المستردَّة والصَّالحة للتَّحليل والَّتي تمَّ تفريغها (98) استبانة. قامت الباحثة بتحليل البيانات باستخدام برنامج التَّحليل الإحصائي (SPSS 20). وفي نهاية هذا البحث توصَّلت الباحثة إلى مجموعة من الاستنتاجات وأهمّها: يوجد تأثير معنوي للعوامل المتعلِّقة بالعميل (شخصيَّة العميل وسمعته، قدرة العميل وخبرته العمليَّة، المركز المالي للعميل، الضَّمانات المقدَّمة من قبل العميل والعوامل الاقتصاديَّة والسِّياسيَّة المحيطة بالعميل) على قرار منح الائتمان المصرفي الصَّغير في المؤسَّسات الماليَّة محل الدراسة. كما تقدَّمت الباحثة في نهاية البحث بمجموعة من التَّوصيات والَّتي كان أهمُّها: ضرورة اهتمام المؤسَّسات الماليَّة محل الدراسة بدراسة شخصيَّة العميل وسمعته للوقوف على مدى رغبته وحرصه على الالتزام بسداد الائتمان الممنوح، وبضرورة طلب وتحليل القوائم الماليَّة لنشاط العميل بهدف ضمان حق المصرف في استرداد أمواله وتجنُّب مخاطر عدم السَّداد، فضلاً عن ضرورة الاهتمام بتنمية الإمكانيَّات الماديَّة والفنيَّة والتكنولوجيَّة والبشريَّة للمؤسَّسات الماليَّة بهدف تقليل الجهد وتسريع الاجراءات وتسهيل خدمة العملاء. This research was conducted to determine the impact of the factors related to the customer (the customer's personality and reputation, the customer's ability and practical experience, the customer's financial position, the customer's guarantees and the economic and political factors surrounding the customer) Which operates in the Syrian coast. The researcher distributed (135) questionnaires on a sample of the employees in the credit department in the financial institutions in the study. The number of questionnaires recovered and valid for the analysis was discharged (98). The researcher analyzed the data using the Statistical Analysis Program (SPSS 20). At the end of this research, the researcher reached a number of conclusions, the most important of which is: There is a significant effect on the factors related to the customer (the customer's personality and reputation, the customer's ability and experience, the financial position of the client, the guarantees provided by the client and the economic and political factors surrounding the customer) Financial institutions under study. In addition, the researcher presented the following recommendations: The importance of financial institutions studied by studying the customer's personality and reputation to determine the extent of his desire and commitment to pay the credit granted, and the need to request and analyze the financial statements of the client's activity in order to guarantee the bank's right to recover its funds and avoid risks As well as the need to pay attention to the development of financial, technical, technological and human resources of financial institutions in order to reduce the effort and speed up procedures and facilitate customer service.